-3x-3=-6x+27

Simple and best practice solution for -3x-3=-6x+27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-3=-6x+27 equation:


Simplifying
-3x + -3 = -6x + 27

Reorder the terms:
-3 + -3x = -6x + 27

Reorder the terms:
-3 + -3x = 27 + -6x

Solving
-3 + -3x = 27 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-3 + -3x + 6x = 27 + -6x + 6x

Combine like terms: -3x + 6x = 3x
-3 + 3x = 27 + -6x + 6x

Combine like terms: -6x + 6x = 0
-3 + 3x = 27 + 0
-3 + 3x = 27

Add '3' to each side of the equation.
-3 + 3 + 3x = 27 + 3

Combine like terms: -3 + 3 = 0
0 + 3x = 27 + 3
3x = 27 + 3

Combine like terms: 27 + 3 = 30
3x = 30

Divide each side by '3'.
x = 10

Simplifying
x = 10

See similar equations:

| 6-4lnx=0 | | 6(9x+9)+2x= | | 2x-1/2x=12 | | 50x-69=0 | | 3z-13z=70 | | 22=2[b+3] | | -14w+3(5w-5)=-8-2(w+12) | | 0.36-1.2x=0.60+x | | -28=a/8 | | 3(n+6)=18-3n | | 12-9x=3-(x+10) | | 6z-3=81 | | 5a-7=-222 | | (K-6)(k-2)+4=0 | | 7-x=x+10 | | k/17=17 | | 144=-16[3+3d] | | 4x^2-8x-12=6x | | -(4-x)=3/4(x-6 | | 35+.14m=67+.10m | | 5+q-16x=-21 | | 19p=171 | | 4y+(y-4)=-20 | | 3(x-8)=-x | | 6a-18/7a-21 | | (2x-3)squared=25 | | 70.92+38.15+52.83= | | 104=-2n-3(4n-2) | | -2x+1=y-5 | | 17=-4n+1 | | 5.7(4+4x)-10.8=12 | | (3n-8)-(-2n+2)= |

Equations solver categories